2019
DOI: 10.1016/j.kint.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine blocks collecting duct cyst growth in Cep164-deficient kidneys

Abstract: Nephronophthisis is an autosomal recessive kidney disease with high genetic heterogeneity. Understanding the functions of the individual genes contributing to this disease is critical for delineating the pathomechanisms of this disorder. Here, we investigated kidney function of a novel gene associated with nephronophthisis, CEP164, coding a centriolar distal appendage protein, using a Cep164 knockout mouse model. Collecting duct-specific deletion of Cep164 abolished primary cilia from the collecting duct epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
(33 reference statements)
3
5
0
Order By: Relevance
“…Together this suggests that CEP164 may have roles in both normal renal development and maintenance of kidney function in the human and mouse. Aberrant CEP164 activity in the kidney could contribute to abnormal primary ciliary function, causing dysregulation of cell division and cell signalling, leading to cystogenesis, which has been suggested in a recent study using murine Cep164 collecting duct cell knockdown [61]. This is consistent with the NPHP-RC phenotype present in most patients with CEP164 mutations [1].…”
Section: Conservation Of Cep164 Expression Was Explored Using a Lacz supporting
confidence: 78%
“…Together this suggests that CEP164 may have roles in both normal renal development and maintenance of kidney function in the human and mouse. Aberrant CEP164 activity in the kidney could contribute to abnormal primary ciliary function, causing dysregulation of cell division and cell signalling, leading to cystogenesis, which has been suggested in a recent study using murine Cep164 collecting duct cell knockdown [61]. This is consistent with the NPHP-RC phenotype present in most patients with CEP164 mutations [1].…”
Section: Conservation Of Cep164 Expression Was Explored Using a Lacz supporting
confidence: 78%
“…In addition, treatment with the mTOR inhibitor rapamycin reduced Cdk1 and Cdk2 activity and attenuated the cystic phenotype, suggesting that the effect of mTOR inhibition is partly mediated by CDK inhibition ( Zhang et al, 2020 ). Finally, roscovitine was demonstrated to attenuate renal cyst progression in a kidney-specific Cep164 -knockout mouse model characterized by rapidly progressive cystic kidney enlargement ( Airik et al, 2019 ). In summary, studies performed mostly in models of infantile NPH have demonstrated that targeting cell cycle dysregulation and proliferation using CDK inhibitors is an efficient approach to limit cyst growth.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…At least six proteins are required for the establishment of the distal appendages ensemble: centrosomal protein 83 (CEP83), centrosomal protein 164 (CEP164), centrosomal protein 89 (CEP89), sodium channel and clathrin linker 1 (SCLT1), Fas binding factor 1 (FBF1), and leucine rich repeat containing 45 (LRRC45) [15,18]. The disruption of the DAP complex results in an impaired ciliary assembly and mutations in genes encoding DAP proteins are characterized by phenotypes affecting various organs associated with ciliopathies [36][37][38][39][40][41].…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…Global Cep164 deficiency in mice leads to early embryonic lethality due to holoprosencephaly, cardiac looping defects, and a truncated posterior trunk [106]. A collecting duct-specific deletion of Cep164 abolishes ciliogenesis and leads to a dysregulated cell cycle and epithelia cell hyperproliferation that drives renal cyst growth [40]. Interestingly, treatment of these mutant mice with a cyclin-dependent kinase inhibitor reduces cortical cyst formation and epithelial proliferation, restoring normal cortical histology [40].…”
Section: Cep164/nphp15mentioning
confidence: 99%
See 1 more Smart Citation